Salvage of foot with extensive giant cell tumour with transfer of vascularised fibular bone graft - Tharayil, Jose (Medknow Publication, 2011)
Though giant cell tumor is not uncommon in young adults, simultaneous involvement of multiple mid-foot bones is very uncommon and very difficult to treat. For reconstruction of large segmental bony defects following tumour excision, free vascularized bone graft is an excellent surgical option. We report a case with extensive involvement of all the tarsal bones and metatarsal bases in a young adult. After excision his foot was reconstructed with vascularised bone flap. We were able to save his foot after a wide local excision and reconstruction with free fibula graft. Graft united early and showed excellent remodelling because of good vascularity. We feel that this method deserves consideration as a last attempt to salvage functional foot in disease like this.